Cross-scale analysis of diversification processes in fuelwood use in three contrasting ecoregions of Argentina (Chaco, Pampa and Patagonia): The role of exotic species in subsistence - Jiménez Escobar, Néstor David (2021)
Fuelwood is an essential source of energy for rural populations in many ecosystems. However, little research has addressed the role of exotic species in relation to the use of native woody plants for fuel. This study was performed in rural communities of three ecoregions of Argentina (the phytogeographical provinces of Chaco, Pampa and Patagonia). Basing our study on the diversification hypothesis, we evaluated whether the exotic species used alongside native plants vary in each region. We also studied diversification in relation to gathering environments and use strategies. Open and semi-structured interviews were conducted in 72 households, focusing on the total richness of fuelwood used and its use pressure. We used the ratio between exotic and native richness as an indirect measure of diversification. Data were analysed qualitatively and quantitatively. A total of 78 species was recorded, of which 51 were native and 27 exotic. Gathering is the most common supply strategy in all the ecoregions studied, fuelwood being obtained mainly in sites with little human intervention. A generalized linear model showed that the use of native versus exotic species varied according to the ecoregion and the level of human intervention in the supply area, while acquisition strategies were similar for both native and exotic species in all ecoregions. The areas with most human intervention were always used to gather exotic plants. In line with our hypothesis, UWPF diversification with exotic species varied according to ecoregion. Intrinsic characteristics associated with the history of each region possibly explain the findings.